Constructing Invisible Walls through National and Global Policy - Stephanie Ettinger de Cuba; Allison Bovell-Ammon; Diana Becker Cutts (MDPI AG, 2019)
Worldwide 37,000 people are forced to flee their homes every day due to conflict and persecution. The factors that lead people to leave their home countries often originate with economic deprivation and violence, escalated to a level that becomes a struggle for survival. Climate change, as it has accelerated over the last three to four decades and negatively impacted natural resources, contributes to a parallel increase in strife and migration. The US response to migration has been to construct an “Invisible Wall” of isolationist and xenophobic policies, many of which are especially harmful to children and their families. The southern US border is perhaps the most high profile location of the Invisible Wall’s construction, fortified by federal policies and a withdrawal from international cooperation. Global reengagement on climate change and migration, US ratification of the Convention on the Rights of the Child, and destruction of the Invisible Wall will help to create a world where children can thrive.